PERKEMBANGAN PENGGUNAAN BETON BERTULANG DI INDONESIA PADA MASA KOLONIAL (1901-1942) - Martha Setyowati (BRIN, 2019)
Abstract The discovery of reinforced concrete became a major breakthrough in modern construction technology in the early 20th century. In five decades reinforced concrete has developed rapidly and was used in almost all parts of the world. Reinforced concrete was first introduced in Indonesia during the colonial period. The used of reinforced concrete increased along with the construction growth in the Dutch East Indies. The used of reinforced concrete between 1901 and 1942 can be seen from the buildings and infrastructure that still exist today. However the development of reinforced concrete in Indonesia during colonial period not widely explored yet. Because of that this study aims to provide an overview of the development of reinforced concrete used during the colonial period using archaeological data and supported by historical data. This research uses secondary data sources obtained through literature study. Based on this research it can be concluded that the development of the reinforced concrete used in the colonial period showed the progress of construction technology as well as economic and social conditions at that time.